1-(3-Aminomethyl-4-hydroxyphenyl)-3-pyridinyl-2-propen-1-ones: A novel group of tumour-selective cytotoxins. (1st October 2013) - Bilginer, Sinan; Gul, Halise Inci; Mete, Ebru; Das, Umashankar; Sakagami, Hiroshi; Umemura, Naoki; Dimmock, Jonathan Richard
Abstract : Two series of 1-(3-aminomethyl-4-hydroxyphenyl)-3-pyridinyl-2-propen-1-ones, designed as novel cytotoxins, were synthesized. The compounds had low CC50 values in the micromolar range against HL-60 promyelocytic leukemic cells and HSC-2, HSC-3 and HSC-4 oral squamous cell carcinomas. The CC50 values of these compounds were higher towards non-malignant HGF (gingival fibroblasts), HPC (pulp cells), and HPLF (periodontal ligament fibroblasts) cells, which reveals the tumour-selectivity of these enones. A representative compound 4c caused cleavage of PARP1 in HSC-2 cells but not in HGF cells, which may be a contributing factor to the tumour-selectivity.